Pengaruh kompetensi auditor, penggunaan analitik big data, dan penggunaan forensik digital terhadap kualitas audit investigatif - Wahyu Nugroho Dwi Kuncoro Aji; Nurhastuty Kesumo Wardhani (LPMP Imperium, 2024)
Investigative audits are crucial in uncovering indications of state losses and criminal acts of corruption in Indonesia. The quality of investigative audits influences the success of the law enforcement process and the justice system's integrity. Factors such as auditor competency, Big Data analytics, and digital forensics are important in improving the quality of investigative audits. This research aims to test the impact of auditor competency, Big Data analytics, and digital forensics on improving the quality of investigative audits. A purposive sampling method was used with 127 BPK auditor respondents. The data analysis method used is multiple linear Regression. The research achievements show that auditor competency, the use of Big Data analytics, and the application of digital forensics significantly impact the quality of investigative audits. BPK institutions should pay attention to selecting auditors with a high level of competency, use Big Data analytics, and apply digital forensic technology to improve their investigative audit performance. Public interest statements This research directly contributes to improving the quality of investigative audits, which has the potential to promote transparency and accountability in public financial management. The findings provide practical guidance for audit institutions to enhance their selection, training, technology, and audit practices, empowering them to make positive changes.